2002
DOI: 10.1248/bpb.25.367
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Effects of Macrophage-Stimulatory Polysaccharide from Leaves of Perilla frutescens var. crispa.

Abstract: The crude polysaccharide (PFB-1) was isolated from the leaves of Perilla frutescens var. crispa by the sequential procedures with hot-water extraction, methanol reflux, and ethanol precipitation. It was further purified by anion column chromatography in order to obtain the partially purified polysaccharide (PFB-1-0). In the presence of PFB-1-0, strong cellular lysosomal enzyme activity of murine peritoneal macrophages was observed in vitro. Compared to bacterial lipopolysaccharide (LPS), its activity was relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…Moreover, MPH may play a positive role in the wound healing process due to its polysaccharide structure, since MPH is a plantbased polysaccharide. Many studies have shown that polysaccharides accelerate the healing process primarily by macrophage activation (13)(14)(15)(16)(17)(18)(19)(20) as well as by fibroblast stimulation (25)(26)(27) and by T-cell stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, MPH may play a positive role in the wound healing process due to its polysaccharide structure, since MPH is a plantbased polysaccharide. Many studies have shown that polysaccharides accelerate the healing process primarily by macrophage activation (13)(14)(15)(16)(17)(18)(19)(20) as well as by fibroblast stimulation (25)(26)(27) and by T-cell stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…MPH particles form a gelled matrix by concentrating blood solids such as platelets, red blood cells, and blood proteins such as, albumin, thrombin and fibrinogen; thus, are used to achieve hemostasis in case of persistent bleeding (11,12). Also, many studies have shown that polysaccharides accelerate and enhance wound healing via various mechanisms, primarily by increasing the activity of macrophages (13)(14)(15)(16)(17)(18)(19)(20). It can be presumed that the MPH can reduce seroma formation by virtue of these characteristics, by preventing the mechanisms causing seroma formation.…”
Section: Introductionmentioning
confidence: 99%
“…pM monolayers were prepared as described previously. 7) Synthetic antioxidants [trolox, N-acetylcysteine (NAC), diphenyl diselenide, butylated hydroxyanisole (BHA)], cyclooxygenase (COX)-1 and -2 dual inhibitors (sulindac sulfone and indomethacin), COX-2 selective inhibitors (meloxicam, nimesulide and NS-398), an inducible nitric oxide synthase (iNOS) inhibitor (1400W), and anti-inflammatory steroids (dexamethasone and hydrocortisone) were purchased from Wako Pure Chemicals Co., Ltd. (Osaka, Japan). Endogenous antioxidants (glutathione and uric acid), natural polyphenolic compounds (gallic acid, (À)-catechin, ferulic acid, and curcumin) and other chemicals were also from Wako Pure Chemicals unless otherwise specified.…”
mentioning
confidence: 99%
“…Data are represented as the mean ± standard deviation for the mean values. The statistical significance was determined by the Student's t-test or ANOVA test with independent means, by using a Microsoft Excel program (15). The critical level for significance was set at P<0.05.…”
Section: Methodsmentioning
confidence: 99%